Randomized Controlled Study of 3D Print Fingerboard and Traditional Fingerboard on Treatment of Stroke Patients with Finger Spasm - Kai WANG; Yiting SHI; Wen HE; Jing YUAN; Yuan LI; Xiaolin PAN; Cuilian ZHAO (康复学报)
Objective:Through the research of scanning, modeling and 3D printing technology, to make personalized 3D print fingerboard, and to observe the effect of 3D print fingerboard in reducing hand spasm and improving hand function of stroke patients in rehabilitation compared with the traditional fingerboard.Methods:A total of 60 cases of hospitalized stroke patients were randomly divided into treatment group and control group, 30 cases in each group, the treatment group treated by custom 3D fingerboard and the control group treated by traditional fingerboard. The compliance, discomfort complaints, hand grip strength, muscle tension, joint mobility and hand function changes were observed respectively at the beginning and after 3 months of treatment.Results:Complete data were obtained in 26 cases in the treatment group and 24 cases of the control group. Compared with the control group after 3 months of treatment, the average time in wearing fingerboard of the treatment group was longer (P<0.01), and the finger muscle tension of the treatment group was lower (P<0.01). Compared with before treatment, the hand grip strength index in the treatment group rose (P<0.01), and the finger muscle tension in two groups decreased and the hand function improved (P<0.01).Conclusion:3D print fingerboard has the features of accurate and personalization as rehabilitation aids. Compared with traditional fingerboard, 3D print fingerboard has more conducive to the treatment of stroke patients with finger spasm.